2019
DOI: 10.1590/1807-3107bor-2019.vol33.0068
|View full text |Cite
|
Sign up to set email alerts
|

Does the implant-abutment interface interfere on marginal bone loss? A systematic review and meta-analysis

Abstract: Meta-analysis Implantodontology Enéias Carpejani ROSA (a) Tatiana Miranda DELIBERADOR (a) Tuanny Carvalho de Lima do NASCIMENTO (a) Cibele Cândida de Almeida KINTOPP (a) Juliana Shaia Rocha ORSI (a) Letícia Maíra WAMBIER (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Few systematic reviews or clinical studies have found no significant differences between internal conical-connection implants and external hexagonal-connection implants in terms of MBL or survival rates [5,6]. Other meta-analyses support the opposite: internalconnection implants have lower MBL compared to external connections implants [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Few systematic reviews or clinical studies have found no significant differences between internal conical-connection implants and external hexagonal-connection implants in terms of MBL or survival rates [5,6]. Other meta-analyses support the opposite: internalconnection implants have lower MBL compared to external connections implants [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…44,45 The accuracy of the space present between the implant interfaces and abutment has high importance for the success of treatments as bacteria can enter through these spaces and produce inflammatory reactions, which can lead to bone resorption and gingival recession. 23,46,47 Kalman reported in three studies 18,37,38 the manufacture of abutments with different materials, in which at first using plastic and metal did not reach the mechanical properties and necessary adaptation for manufacture provisional. 37 However, after optimizing the design, using the titanium alloy Ti6Al4V in two other studies, 18,38 was successful in the adaptation and tightening of the abutment, which presented the maximum torque of 49.9 N/cm to the implant for manufacturing provisionals.…”
Section: Discussionmentioning
confidence: 99%
“…As an implant filling material, PTFE membranes are flexible, minimizing the potential bacterial leakage and creating a better long-term seal. However, the leakage from the abutment-implant interface and the abutment screw access channel cannot be eliminated, and the penetration and colonization of bacteria cannot be prevented entirely [7]. Hence, new dental implant filling materials with antibacterial properties are needed to inhibit microbial attacks.…”
Section: Introductionmentioning
confidence: 99%